Digital media-based learning in improving the quality of Islamic religious education learning at the integrated Islamic vocational high school of Tebuireng III Indragiri Hilir Riau - Nurqozin, Muhamad; Samsu; Putra, Darma (Eximia, 2023)
Islamic education is currently faced with various developments which of course to make changes and improvements must be able to adapt to these changes. The development of science and technology (science and technology) is a challenge for Islamic Education, especially when faced with the era of globalization which has been able to cover distance and time between various countries in exchanging information and knowledge, especially in the field of Islamic Education. The aim of this research is to describe and analyze (1) the digital media used in digital media-based PAI learning, (2) the implementation of digital media-based PAI learning, (3) the impact of digital-based media in improving the quality of PAI learning at Integrated Islamic Vocational School Tebuireng III Indragiri Hilir Riau. This research uses a qualitative approach with a case study type of research. Data collection techniques through observation, interviews and documentation. Data is analyzed through data collection, data condensation, data presentation and drawing conclusions. Checking the validity of the data includes techniques for extending participation, diligent observation, triangulation, and discussions with friends. The research results show that: (1) There are two forms of digital media used in PAI learning: The first is digital media that does not use an internet network such as laptops, projectors, power points, speakers, etc. The second is digital media that uses the internet network in its use, such as gamma.app, AI, e-books, YouTube, websites, web pages, CBT, and others. Learning refers to government regulations, teachers are active in the MGMP group, preparing learning plans according to the objectives, materials, and needs of students. Teachers prepare learning resources, namely PAI e-books, learning videos, power points, articles related to PAI material and share them on Google Classroom. (2) The implementation of digital media-based PAI learning consists of preliminary activities: the teacher tries to condition the students when learning begins, taking attendance, conducting apperception and conveying basic competencies and the material to be studied. Teachers apply a scientific approach: observing, asking, collecting, reasoning and communicating. Ends with reinforcement, assignments, prayers and greetings. (3) The impact of digital-based media on the quality of PAI learning has positive and negative sides. Positive aspects, namely: students are more enthusiastic in implementing learning, teachers are more skilled in the teaching process, can foster student enthusiasm in the learning process, make it easier for teachers to deliver material and can adjust time and improve student learning outcomes. Meanwhile, the negative side is that some students have difficulty making ppt and there are still students who secretly access the internet outside of PAI learning materials.